Design of Controllers for Continuous Stirred Tank Reactor - Somasundaram Deepa; N. Anipriya; R. Subbulakshmy (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
The objective of the project is to design various controllers for temperature control in Continuous Stirred Tank Reactor (CSTR) systems. Initially Zeigler-Nichols, modified Zeigler-Nichols, Tyreus-Luyben, Shen-Yu and IMC based method of tuned Proportional Integral (PI) controller is designed and comparisons are made with Fuzzy Logic Controller. Simulations are carried out and responses are obtained for the above controllers. Maximum peak overshoot, Settling time, Rise time,  ISE, IAE  are chosen as performance index. From the analysis it is found that the Fuzzy Logic Controller  is a promising controller than the conventional controllers.